(untitled) (Annals of Medical Research, 2021)
Aim: The expression of villin protein is widely used to determine to the gastrointestinal origin of metastatic tumors. However, little is known about the prognostic value of villin expression in colorectal cancer (CRC). The aim of this study is to investigate the relation between villin expression and basic histopathological features and survival in CRC. Secondarily, investigation of the prognostic significance of the CD4+/CD8+ TILs ratio was adopted. Materials and Methods: Villin expression and CD4+/CD8+ TILs ratio were evaluated in paraffin-embedded tumor tissues of 147 CRC patients, immunohistochemically. Results: Decreased villin expression was clearly detected in the tumoral areas compared to non-tumoral colonic mucosa. Loss of villin expression was closely related to high depth of tumor invasion (P = 0.001, ANOVA), increased lymph node metastasis (P <0.001, ANOVA) and high distant metastasis rate (P <0.001, t-test). These findings exposed that decreased villin expression is effective in the progression and aggressiveness of CRC. In addition, high villin expression was closely associated with low overall (p <0.001, Log Rank) and disease-free survival times (p <0.001, Log Rank). Furthermore, multivariate analyses revealed decreased villin expression was independently related with short overall (HR 5.82, 95% CI 3.18-10.65, p <0.001) and disease-free survival (HR 4.08, 95% CI 2.67-6.25, p <0.001). The mean CD4+/CD8+ TILs ratio of all patients was 1.73±1.74 (range 0.14-8.0). High CD4+/CD8+ TILs ratio was positively correlated with high pT and advanced TNM stage (p <0.001, ANOVA). In the univariate Cox regression analyses the high CD4+/CD8+ TILs ratio was an importantly correlated with poor overall outcome (HR 2.22, 95% CI 1.46-3.38, p <0.001). Conclusion: Decreased villin expression and high CD4+/CD8+ TILs ratio are associated with aggressive pathobiological behavior in CRC. Moreover, decreased villin expression is an independent poor prognostic indicator.